Ductile damage of AA2024-T3 under shear loading: Mechanism analysis through in-situ laminography. (15th February 2021) - Tancogne-Dejean, Thomas; Roth, Christian C.; Morgeneyer, Thilo F.; Helfen, Lukas; Mohr, Dirk
Abstract: The mechanisms leading to fracture of aluminum alloy AA2024-T3 under shear loading are investigated via X-ray synchrotron laminography. A 1mm-thick flat double-gage section shear specimen is loaded inside a synchrotron X-ray beamline. The microscale defects population is reconstructed on six loading steps as well as on the broken specimen. The material exhibits an initial void volume fraction of 0.7% as well as a high concentration of large Cu-rich intermetallic particles. Using 2D Digital Image Correlation of projected volume data, based on the void contrast, it is possible to track the evolution of both types of mesoscale defects throughout the loading and to correlate the deformation mechanisms with the local strains. Upon mechanical loading, pre-existing voids rotate and elongate following the deformation of the aluminum matrix. The intermetallic particles fail at early loading stages in a brittle manner, leading to the nucleation of voids normal to the maximum principal stress direction. The newly-created voids continue to grow during the subsequent loading steps impeded by the fragmented particles, eventually forming micro-cracks. A fracture mechanism is proposed based on these observations and assessed with a representative volume element simulation, pointing towards the formation of a shear localization band during the final loading step. Graphical abstract: Image, graphical abstract